Skill Demands of Vietnamese Textile and Footwear Enterprises in the Context of Digital Transformation - Kim Khanh Ly, Dang; Thu Trang, Nguyen (VNU Journal of Science: Policy and Management Studies, 2025)
Digital transformation and the Fourth Industrial Revolution are fundamentally reshaping skill requirements in Vietnam’s textile and footwear industries. This paper examines the issue from the perspective of business owners and human resource managers, with the aim of identifying current skill gaps and forecasting future workforce demands in the sector. Drawing on survey data from 50 textile and footwear enterprises across the country, the study analyzes skill needs and the challenges businesses face in recruitment and training. The findings indicate that most companies perceive their current workforce’s skills as only moderately aligned with job requirements. Emerging competencies—such as digital literacy, the ability to operate advanced machinery, and problem-solving skills—are becoming increasingly essential. Over half of the surveyed enterprises report a shortage of skilled labor, particularly in technical and managerial roles. Many also face significant difficulties in recruitment and training, largely due to the limited supply of qualified workers, time constraints, and financial limitations. These findings underscore the urgent need for human capital development and highlight the importance of more proactive and strategic human resource approaches in the digital era.